On Modeling the Physical World as a Collection of Things: The W3C Thing Description Ontology - Charpenay, Victor; Käbisch, Sebastian (The Semantic Web, 2020)
This document presents the Thing Description ontology, an axiomatization of the W3C Thing Description model. It also introduces an alignment with the Semantic Sensor Network ontology and evaluates how this alignment contributes to semantic interoperability in the Web of Things. <br
Keywords: Web of Things; Thing Description; SSN; RDF